The Perspective of Food Delivery Courier in Semarang Toward Safety Riding - Fatimah; Andromeda, Vega Fonsula; Pujiantoro, Wisnu (RSF Conference Series: Engineering and Technology, 2023)
The Economy creates many e-commerce that increase the number of couriers including food delivery couriers. This group has the potential to have near-miss crash accidents. This study explored the perceptions of food delivery couriers in Semarang about safety riding. In this study, 50 participants were chosen using the purposive sampling method. Web-based questionnaires were deployed to collect data. The questionnaire was to elicit about the participants’ perceptions and work experience as well as the training. Data were analyzed using descriptive statistics. The result of the study revealed that the courier had a positive perception towards the use of safety riding. Most of them agree that they should obey the rules to make them safe and use safety riding equipment such as helmets, jackets, gloves, and shoes. However, some of them still had negative perceptions about the workload and the speed limit in riding. Some of them think that they can have a maximum speed at work although it will not be safe for them. Many couriers also think that it is OK to work in more than two workplaces. The recommendation is to give them training about safe riding.